An Activity-Theoretical Method for Studying User Participation in IS Design - Hyysalo, S.; Lehenkari, J. (Methods of Information in Medicine, 2003)
Objectives: This paper aims to present an activity-theoretical method for studying the effects of user participation in IS development.Methods: This method is developed through a case study of the process of designing a diabetes database.Results and Conclusions: The method consists of a historical analysis of the design process, an ethno-graphical study of the use of the database, and researcher-driven interventions into the on-going user-producer interaction. In the historical analysis, we study particularly which user groups of the database have influenced the design work and which perspectives need to be incorporated into the design in the near future. An analytical model consisting of perspectives on local design, particular technology, and societal domain is introduced as a conceptual tool for this analysis. We also introduce the possibility of employing the historical analysis in guiding an ethno-graphical study of the user sites and researcher-driven interventions, which provide the participants with tools for improving their design process.
Keywords: Diabetes databases; activity theory; historical analysis; ethnography; interventions